Urban Quality vs Single Travel: the Personal Rapid Transit - Carmela Gargiulo (TeMA: Journal of Land Use, Mobility and Environment, 2011)
The great increase in the demand for private mobility with theconsequent macroscopic growth of channels to meet it, togetherwith short-sighted policies of transport and urban developmentspread above all in Italy, has produced pollution, congestion andunlivability in the last fifty years.The hope of assuring the maximum individual freedom of travel topeople living in consolidated urban centres, in addition to thoseliving in the outskirts arisen and developed without any reasonableurban logic, still goes on producing congestion of vehicular traffic,considered, by the majority of citizens, the main cause of thedeterioration of the quality of life in our cities.Indeed, also the most recent reports on environment in Italiancities show that the pollution levels are increasing in the big cities,although the news are full of very expensive projects, innovativesolutions and unexpected goals continuously shown by publicadministrations. One of the main environmental detractors is cartraffic, which has recently gained on public transport. unlike theprevious period.Most of mobility policies implemented in our cities aims at reachingthe modal balance by means of measures for controlling and managingthe demand for mobility, for mitigating traffic and limiting circulation.,such as the road pricing and the parking strategies; for developingand increasing public transport and not polluting means of transport,car sharing and car pooling.All of them have showed modest results both in terms of pollutionreduction and vehicular traffic reduction.For over fifty years, mostly in the United States, the Personal RapidTransit has been tested, a system of public transport trying to jointwo apparently incompatible factors: the possibility of assuringindividual travels and the need for decreasing the levels of acousticand air pollution as well as the congestion caused by privatevehicular traffic.In Italy this system is still not well known despite the versatility ofits fields of application. In the United States and all over the worldthe most successful applications concern circumscribed monofunctionalurban ambits, such as large areas for offices, airportsand so on, but the characteristics of this system - such as flexibility,capability of integration with other wide-range systems of publictransport, little dimensions of the exchange junctions, quite lowcost - can allow to realize it also in different typologies of area.If many people are doubtful about the effectiveness of this system,on the contrary, other people think that its steady implementationand experimentation is necessary to improve urban liveability.These last ones believe, in fact, that the combination of small vehiclessimilar to private car, the advantage of trips without intermediatestops and changes of car, cost reduction, possibility of a wideraccessibility not reachable by traditional means of public transportare the key basic elements to replace car travels with low pollutingmeans of public transport.